Shelf life extension of banana using edible surface coatings conjugated with silver nanoparticles - Jafarizadeh Malmiri, Hoda (2012)
Banana is one of the most favoured specialty tropical fruits and is very popular world-wide. Short shelf life of banana limits the storage, handling and transport potentials of the fruit. ‘Berangan’ banana (Musa sapientum cv. Berangan) is one of the most popular dessert cultivars and very highly priced in Malaysia. In the present study, edible coatings incorporated with silver nanoparticles as an alternative packaging were used in combination with low temperature (15+1'C and 65+10% RH) storage to extend the shelf life of banana. Green mature ‘Berangan’ bananas were coated using eight different edible coating formulations based on polysaccharides and proteins and stored at ambient conditions (26+2'C and 45+5% RH). Results of physico-chemical analysis of coated and control banana samples at day 10 of storage, indicated that edible coatings based on chitosan – glycerol – Tween 80 and sodium carboxymethyl cellulose (Na-CMC) – sodium caseinate (Na-Cas) – glycerol were more effective in slowing ripening process of banana among all different edible coating formulations selected based on literature review. Optimum concentrations of edible components of these two selected coating formulations were obtained using response surface methodology (RSM). Optimum concentrations of chitosan, glycerol and Tween 80 were 2.02%, 0.18% and 0.1% (w/w), and for Na-CMC, Na- Cas and glycerol, the optimum concentrations were 1.32%, 0.40% and 0.86% (w/w), respectively. Silver nanoparticles (SNPs), as a strong antimicrobial agent, was incorporated in the optimized edible coating formulations based on chitosan and Na-CMC. Due to high antimicrobial activity of edible coating based on chitosan, addition of small amount of SNPs (0 – 90 mg l-1) to this coating formulation, did not show significant (p> 0.05) effect on antimicrobial properties of resulting coating. The minimum bactericidal concentration (MBC) of SNPs to be incorporated into the edible coating formulation based on Na-CMC was 60 mg l-1. Application of the optimized edible coatings based on chitosan – glycerol –Tween 80 and Na-CMC – Na-Cas – glycerol with and without SNPs, at a concentration of 60 mg l-1, on green mature ‘Berangan’ banana followed by storage at both ambient (26+2'C and 7010% RH) and low temperature (15+1'C and 65+10% RH) conditions, indicated that all these three coating formulations could increase the shelf life of bananas stored at ambient and low temperatures by 3 days and 1 week, respectively. The maximum shelf life of control banana samples stored at ambient and low temperatures were 15 days and 5 weeks respectively. Results of the present study revealed that there was no significant (p> 0.05)differences in the most of physico-chemical, physiological and sensory attributes between banana samples coated with coating formulations based on Na-CMC – Na-Cas – glycerol with and without SNPs. The coating formulations based on chitosan and Na-CMC conjugated with SNPs, significantly (p< 0.05) inhibited growth of bacteria, yeasts and moulds on the banana surface, while the coating formulation based on Na-CMC without SNPs did not show inhibition effect on microbial growth, during storage at ambient and low temperatures. Evaluation of penetration of SNPs in both peel and pulp of coated banana samples with coating formulation based on Na-CMC – Na-Cas – glycerol – SNPs, indicated that during the ripening of coated banana samples, 92.5% and 90% of the SNPs which penetrated into the banana peel were detected in the outer layer of peel and the rest were detected in the inner layer of peel at both ambient and low temperature conditions, respectively. No SNPs were detected in the banana pulp, at both storage conditions. This could be due to the thickness and structure of banana peel. ‘Berangan’ banana is a thick-skinned banana and cell wall of its peel is composed of pectic, cellulose and hemicellulose components. These cell wall components of the peel can strongly create ionic bonds with SNPs and decrease their penetration rate through the banana peel. Thus, no SNPs could penetrate the pulp.